Entrepreneurship Education Pedagogical Approaches in Higher Education - Ana Luísa Rodrigues (MDPI AG, 2023)
Entrepreneurship education, as an emerging scientific field, has undergone significant evolution at the conceptual and praxis levels. The concept of entrepreneurship was considered from a broad perspective as the capacity to act upon opportunities and ideas, thereby creating social, cultural, or financial value in diverse contexts. The study and cultivation of this competence are highly relevant to enhancing employability and equipping young people with the skills, knowledge, and attitudes necessary within an entrepreneurial culture for the exercise of active citizenship. This study aims to consolidate the concept and analyse the pedagogical approaches in entrepreneurship education, particularly focusing on experiential learning. It also explores the most frequently used instructional methods in higher education programmes. The research is based on a comprehensive literature review, complemented by a case study of the entrepreneurship education programme implemented at the University of Lisbon, in Portugal, enriched by data collected from one of its curricular units. Experiential learning emerges as a valid approach in entrepreneurship teaching, especially when teachers effectively combine practical experience with theory while learners assume the shared responsibility of learning from experience. As the most recommended instructional methods, one can point to collaborative pedagogical models, namely problem-based learning, project-based learning, peer assessment, design thinking, formative feedback, service learning, and active methodologies that integrate digital technologies.